Development of a teacher competency model in game-based learning: a need analysis - Jiang, Jinchuan; Abu Ziden, Azidah (Institute of Advanced Engineering and Science, 2025)
This paper conducts a need analysis study to identify the requirements for developing a competency model for teachers implementing game-based learning (GBL) in Chinese secondary schools. Additionally, it investigates the practices and challenges of teachers while implementing this pedagogical approach. Through a quantitative survey involving 384 teachers, key findings reveal significant challenges, such as technological issues, limited instructional time, a lack of high-quality games aligned with the curriculum, and inadequate teacher training. The majority of teachers expressed a positive attitude towards game-based learning but reported limited classroom usage due to these obstacles. The results highlight the need for the development of a competency model tailored to game-based learning teachers, emphasizing the importance of structured training opportunities. Such a model would provide essential guidance and support, enabling teachers to enhance their competencies and effectively integrate game-based learning into their teaching practices. Consequently, the next step of this research is to design and develop a comprehensive competency model that encompasses both technological and pedagogical skills, which will aim to enhance teacher preparedness and improve the integration of game-based learning in education, ultimately benefiting student engagement and learning outcomes.